Biblioteca – „al treilea spațiu”: regândirea bibliotecii ca spațiu - COȘERI, Tatiana (BIBLIOPOLIS, 2025)
The article outlines the distinctive features of library spaces where people gather for the pleasure of reading, conversation, shared experiences, and social interaction. These spaces are examined both as architectural and physical elements and as enablers of new skills or emotions. Both dimensions create values that transform individuals and communities. The “third place” is defined as a setting where people come to momentarily set aside concerns related to personal or professional life. It is not merely a multifunctional infrastructure but also a social product that fosters knowledge, human connection, and change. Libraries embody the essential characteristics of this “third place”.